PENINGKATAN KEAMANAN DATA END-TO-END SMART DOOR MENGGUNAKAN ADVANCED ENCRYPTION STANDARD - Adhiwibowo, Whisnumurti; Hirzan, Alauddin Maulana; Suprayogi, Muhammad Sani (P3M Politeknik Negeri Banjarmasin, 2022)
Smart Home is one form of implementation of Internet of Things technology in the form of smart homes that can carry out management, monitoring, even reporting. In addition, smart homes can be equipped with security equipment such as Smart Door that can open or lock the door automatically when recognizing the homeowner's face. However, the current Smart Door model has a disadvantage where the stored data on the server and the device are not secured end-to-end. The homeowners' image data on the device is not encrypted with a specific algorithm and validation. Thus, the outside parties can use this high-risk problem to enter the house unnoticed. They disguised themselves as the homeowner by entering false data on the device. Based on this problem, this study has a purpose to increase the model's end-to-end security by implementing the Advanced Encryption Standard algorithm. In addition to increase the security level, the Truncated Decimal-converted SHA-1 checksum validation is added to prevent modifications in each image data. From the results of the model comparison experiment, there was an increase in device resource needs as much as 0.81% increase in process time; 18% CPU usage; 5.3% data usage; and 5.04% for the use of the entire process of memory. But the increase in performance needs is not comparable to the security features presented by the Advanced Encryption Standard algorithm in securing data and servers. So that with improvisation this security is expected to improve the data security of homeowners from outside parties.